Tort Bonding Sale Agreement (SPA) Made by Notary (Study Decision Number: 17 / Pdt.G / 2011 / PN.Smg) - Fertin Fertin; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
SPA is a preliminary agreement on the purchase agreement of land rights which the agreement will be drawn up and signed in the presence of PPAT, a description of relevant scientific writing case of default in Decision 17 / Pdt.G / 2011 / PN.Smg. Issues examined in this study is enforceable agreement of sale and purchase agreement (SPA) Notary as evidence of authentic, legal consequences if one of the parties in the agreement binding sale and purchase (SPA) has been in default as well as legal protection of the fulfillment of the rights of parties where one party is in default in a binding sale and purchase agreement. The method used in this research is the socio-legal approach that comes from the collection of the data obtained from the primary data and secondary data, and then analyzed by qualitative analysis method. The study provides an answer that the legal force PPJB made before a notary public as authentic evidence in the transfer of rights agreement is very strong. Regarding the legal consequences if one party has been in default then the agreement was null and void, in addition to the legal protection of the fulfillment of the rights of the parties where one party is in default is a return to power of the SPA were made, namely if made before a Notary Public, perlindunganya force in accordance with the protection of an authentic agreement.Keyword: Bonding Sale Agreement (SPA); Notary; Legal Consequences.